Trends dan Dampak Penelitian Halal Tourism Dunia: Meta Sintesis dan Blibliometric Analysis - Lubis, Alya Syafitri; Azhar, Azhar; Naurah Athaya (Universitas Medan Area, 2024)
Researchers about the world's Muslims have presented a collection of scientific works on halal tourism in many countries. The positive impact of tourism can be seen in terms of social, cultural, environmental, and economic. This article aims to see the trends and impact of the development of research on halal tourism around the world. To approach this problem, bibliometric analysis is used as a method that can map research specialization, and the meta-synthesis method as a technique for integrating data to obtain broader results. This study concludes that there are 25 top countries identified in publications related to halal tourism. The impact of halal tourism is positive on the economic sector, so the results of the literature explain that halal tourism brings foreign exchange, especially in the tourism sector.